2018
DOI: 10.1080/03007995.2018.1464435
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity with healthcare resource utilization and costs in a commercial population

Abstract: Increasing BMI was associated with higher prevalence of cardiometabolic conditions and higher HRU and costs. There is an urgent need to address the epidemic of obesity and its clinical and economic impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Among Weight Loss Maintainers, those with the greatest weight loss had lower overall healthcare utilization, except for hospitalizations. Healthcare resource utilization did not demonstrate expected trends as it has been shown that obesity is associated with higher healthcare utilization [ 48 , 49 ]. Future studies will need to explore the relationship between healthcare utilization and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Among Weight Loss Maintainers, those with the greatest weight loss had lower overall healthcare utilization, except for hospitalizations. Healthcare resource utilization did not demonstrate expected trends as it has been shown that obesity is associated with higher healthcare utilization [ 48 , 49 ]. Future studies will need to explore the relationship between healthcare utilization and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Higher medical care costs among individuals with obesity have been found for a variety of U.S. subgroups across various data samples using several different research methods. [11][12][13][14][15] Previous research has shown that medical expenditures associated with obesity vary by state, both overall and by type of payer. [16][17][18][19][20] For example, Biener et al (2018) reported that the proportion of medical expenditures associated with obesity ranged from approximately 4% in California to 14% in North Carolina in 2015, based on estimates from the Medical Expenditure Panel Survey (MEPS).…”
Section: What This Study Addsmentioning
confidence: 99%
“…Together with the multitude of comorbidities (diabetes, cardiovascular disease, cancer, etc.) associated with obesity and increased healthcare costs corresponding with higher BMI classifications [4][5][6][7][8][9], it is important to use big data sources to understand at the population-level variations in health outcomes of those with obesity; the stratification by BMI classifications may also provide a more in-depth understanding of the impact of obesity severity on health outcomes. The utility of this RWE generation, particularly when combined with other big data technologies (e.g., genomics, metabolomics, information collected by personal monitoring devices, GPS, Fitbit), can be explored under the infrastructures of health system disease management and public health surveillance and interventions [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The BMI is predictive of greater risk for multiple disease conditions, including metabolic syndrome, type II diabetes, cardiovascular disease, some cancers, liver and kidney disease, arthritis, asthma, and depression, as well as a greater risk for all-cause mortality [4][5][6]. Additionally, variations in BMI are predictive of healthcare resource utilization and costs [7][8][9]. The health risks associated with obesity and its high prevalence in the US [4] necessitates the study of populations with obesity on several inter-related facets, such as population sociodemographic and clinical characteristics, current and emerging health outcomes and costs, value of therapeutic interventions, patient-drug/procedure interactions, etc.…”
Section: Introductionmentioning
confidence: 99%